Quality evaluation of Arnebia euchroma with different growth years based on metabolomics and antioxidant activity - Obul, Zumrat; Qiu, Yuan-jin; Zhao, Ya-qin; Zhu, Jun; Wang, Guo-ping; Song, Wen-dan; Rehmetulla, Aybek; Fan, Cong-zhao; Zhang, Ji-zhao (Frontiers in Plant Science, 2026)
IntroductionArnebia euchroma (Royle) Johnst., a perennial herb in the Boraginaceae family, is valued for its medicinal properties. The harvesting period is crucial for ensuring both the quality and yield of this medicinal material. However, gaps in the knowledge of its optimal harvesting period impede the establishment of standardized cultivation and quality control protocols. This study aims to analyze the quality variations and their dynamic patterns in A. euchroma across different growth years, to provide evidence for determining its optimal harvesting time.MethodsThis study used roots from 2- to 7-year-old A. euchroma as the research material. Fresh and dry root weights across multiple growth stages were compared, and key marker compounds were quantified using Ultraviolet–visible(UV) spectrophotometry and High Performance Liquid Chromatography(HPLC). At the same time, metabolite accumulation patterns were profiled via Ultra High Performance Liquid Chromatography-Tandem Mass Spectrometry(UHPLC-MS) untargeted metabolomics. We also applied network pharmacology to identify potential bioactive constituents, and their in vitro antioxidant activity was evaluated using 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric ion reducing antioxidant potential (FRAP) assays.ResultsThis study demonstrated that the fresh and dry weights of A. euchroma roots increased steadily and consistently with increasing growth years. Total hydroxynaphthoquinone pigments followed a “rise-decline-rise” trend, The content ranged from 1.73% to 4.44%. The concentration of β,β′-dimethylacrylshikonin increased steadily from 0.11% in 2-year-old plants to 0.52% in 7-year-old plants. Untargeted metabolomic analysis identified 1,058 metabolites, including 355 differentially accumulated metabolites (DAMs). K-means clustering of DAMs revealed distinct accumulation patterns: flavonoids, phenolic acids, polyketides, phenylpropanoids, and fatty acids peaked in 4-year-old plants. Network pharmacology analysis identified 14 potential bioactive compounds, with notably high expression levels in 4- and 7-year-old plants. In vitro antioxidant testing revealed that antioxidant activity peaked in 4-year-old plants under DPPH and FRAP assays, whereas ABTS scavenging ability was most pronounced in 6-year-old plants.DiscussionThese findings elucidate the quality variations and seasonal dynamics of A. euchroma. Across growth years, a comprehensive evaluation identifies the 4-year growth period as the optimal harvest timing for A. euchroma, providing a reference for the development of standardized harvesting and quality control protocols.